Instagram Social Media As A Means Of Supporting Information And Promotion At PT. AIK Cheong Indonesia - Sendy Zul Friandi; Indri Handayani; Ferinda Kusuma Ratih (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2021)
Currently, the development of the world of information technology is growing rapidly, and information is important because, with information, everyone can easily get what they want. Dissemination of information is the dissemination in the form of multimedia through print media or electronic media, from which the public can obtain information. PT. Aik Cheong Indonesia is a distributor of Lacha Malaysia on Jl, Indonesia. Imam Bonjol Panunggangan Barat, Cibodas District, Tangerang City, PT. Aik Cheong Indonesia, the time of its establishment was not long enough. PT. Aik Cheong Indonesia, relatively new, still uses oral and written media, PT. Aik Cheong Indonesia needs Instagram social media to support information and promotion of PT. Aik Cheong Indonesia informs the public, especially potential customers, that they are interested in ordering various products from PT. Yichang Indonesia. Currently, the types of media that support information vary. Social media is an information promotion and promotion strategy developed by companies to increase revenue. Social media that can provide information to the public can communicate well. For the community, the information generated in this way can add value, selling point, and company pride, as an alternative problem solution. It is necessary to design effective promotional media in the form of Instagram social media to attract the attention of all potential consumers. Social media that can provide information to the public can communicate well. For the community, the information generated in this way can add value, selling point, and company pride, as an alternative problem solution. It is necessary to design effective promotional media in the form of Instagram social media to attract the attention of all potential consumers. Social media that can provide information to the public can communicate well. For the community, the information generated in this way can add value, selling point, and company pride, as an alternative problem solution. It is necessary to design effective promotional media in the form of Instagram social media to attract the attention of all potential consumers.